Masseter muscle contraction and cervical muscle sensitization by nerve growth factor cause mechanical hyperalgesia in masticatory muscle with activation of the trigemino‐lateral parabrachial nucleus system in female rats. Issue 10 (2nd November 2022) - Kubo, Asako; Sugawara, Shiori; Iwata, Koichi; Yamaguchi, Satoru; Mizumura, Kazue
Abstract: Objective: To establish a new rat model of craniofacial myalgia, and to clarify which central nervous system pathways are activated in the model. Background: Craniofacial myalgia, represented by myogenous temporomandibular disorder and tension‐type headache with pericranial tenderness, is more common in female patients. The pain is thought to be a type of multifactorial disorder with several coexisting causes. To our knowledge, there are no models of craniofacial muscle hyperalgesia caused by multiple types of stimuli. Methods: We injected nerve growth factor into the trapezius muscle of female and male rats and repeatedly stimulated the masseter muscle (MM) electrically for 10 days. We determined the mechanical head‐withdrawal threshold of MM and extent of phosphorylated extracellular signal‐related kinase 1/2 (pERK) immunoreactivity in various regions of the lower brainstem. We conducted retrograde tract‐tracing to determine the projection of mechanosensitive MM‐innervating secondary neurons to the lateral parabrachial nucleus. Finally, we administered morphine in rats to determine whether increases of pERK immunoreactivity were dependent on noxious inputs. Results: In female rats, but not male rats, the mechanical head‐withdrawal threshold was decreased significantly from days 9 to 12. The number of pERK‐immunoreactive neurons in the brainstem was increased significantly in female rats in the group with both stimuli compared to rats in other groups with a single stimulus. Mechanosensitive MM‐innervating neurons in the brainstem projected to the parabrachial nucleus. Morphine administration blocked the increase in the number of pERK‐immunoreactive neurons in both the brainstem and parabrachial nucleus. Conclusions: We established a model of craniofacial myalgia by combining trapezius and MM stimuli in female rats. We found mechanical hyperalgesia of the MM and activation of the pain pathway from the brainstem to parabrachial nucleus. The model reflects the characteristics of patients with craniofacial myalgia and might be helpful to clarify the pathogenic mechanisms underlying these disorders.